Clinical Course and Clinical Features in MDD Patients: General and Specific Role of Subtypes of Childhood Traumaψ. (July 2021) - Li, Xianbin; Tan, Tony Xing; Bo, Qijing; Mao, Zhen; Li, Feng; He, Fan; Dong, Fang; Ma, Xin; Wang, Chuanyue
Our study focused on childhood emotional neglect and several forms of abuse (i.e., physical, sexual, and emotional) and the diagnosis and clinical courses of disease in Chinese adults with major depressive disorder (MDD), including MDD with anxiety, with suicidality, and with other presentations. MDD and other clinical presentations were determined with the American Psychiatric Association's (2000) Diagnostic and Statistical Manual of Mental Disorders (4th ed.; DSM-IV) and subtypes of trauma were assessed with the Childhood Trauma Questionnaire (95 patients and 94 comparisons). Patients with MDD and suicidality scored higher on childhood emotional abuse and neglect than other MDD patients. Both emotional abuse and physical abuse correlated with a younger age of onset and more relapses of MDD. General linear modeling also showed that controlling for demographic variables, emotional and physical abuse predicted more MDD relapses. Overall, childhood trauma was correlated with a MDD diagnosis, the role of specific types of trauma in the clinical courses of MDD varied.